2019
DOI: 10.1177/2042098619846993
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of cannabinoids for the treatment of neuropsychiatric symptoms in dementia: a systematic review

Abstract: Background: Neuropsychiatric symptoms (NPS) in dementia impact profoundly on the quality of life of people living with dementia and their care givers. Evidence for the effectiveness and safety of current therapeutic options is varied. Cannabinoids have been proposed as an alternative therapy, mainly due to their activity on CB1 receptors in the central nervous system. However, little is known regarding the safety and effectiveness of cannabinoid therapy in people with dementia. A literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
0
29
0
1
Order By: Relevance
“…47,48 In addition, cannabinoid use by the elderly can lead to impairment that may lead to unintended injuries like falls. 49 While several reviews 4,13,15,29,30,45,[50][51][52][53][54][55][56] have been published on the topic of cannabinoids for dementia, most have provided only systematic reviews, and not quantitative synthesis. A prior Cochrane systematic review from 2009 57 identified only a single trial 37 -precluding any formal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 In addition, cannabinoid use by the elderly can lead to impairment that may lead to unintended injuries like falls. 49 While several reviews 4,13,15,29,30,45,[50][51][52][53][54][55][56] have been published on the topic of cannabinoids for dementia, most have provided only systematic reviews, and not quantitative synthesis. A prior Cochrane systematic review from 2009 57 identified only a single trial 37 -precluding any formal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Distinctions should be made between disease-modifying and symptomatic benefits, where generally cannabinoids have been more likely to provide variable benefits in the latter. For example, in clinical dementia trials reporting treatment of patients with phytocannabinoids, some trials reported significant improvements in a range of neuropsychiatric symptoms, whereas other trials returned no significant benefit [ 156 ]. Where symptomatic benefit is observed, it is more commonly reflected in decreased agitation and aggression, increased appetite, sleep quality, objective mood and pain control [ 8 ].…”
Section: Clinical Studies In Dementiamentioning
confidence: 99%
“…Observational studies have also shown promising results, particularly in cases with refractory symptoms. 117 Two of three recent meta-analyses were unable to show conclusive results for cannabinoid efficacy in the treatment of agitation or aggression. 118,119 The most recent meta-analysis, however, was able to show significant improvement in different NPS instruments and efficacy was associated with baseline dementia severity and dose.…”
Section: Treatment Of Noncognitive Symptoms Of Dementiamentioning
confidence: 99%